Uniqueness of the Ornamentation and Design of the Wooden Beam System in Jiangnan Traditional Architecture: Wan Motif on Baofujin Color Paintings on Gaoyang Bridge in China - Li, Jian; Yahaya, Siti Rohaya (Journal of Ecohumanism, 2024)
The vulnerability of vernacular architecture places the wooden structures and color painting decorations of traditional Chinese architecture at risk of gradually disappearing from history. The Chinese character for wan (卍; also pronounced wan), which is a homonym for the Chinese character wan (万, meaning “10,000”), is a common artistic element in traditional Chinese architectural color painting. However, the wan pattern in the Gaoyang Bridge color paintings exhibits a distinctive composition form and thus creates a novel theme for the Baofujin color painting art. This study uses a qualitative case study combined with a field survey and observational study to explore the uniqueness of the design form of the wan pattern and its profound symbolism in the Gaoyang Bridge Baofujin color painting. In addition, this study proposes methods and suggestions for preserving and developing this decorative technique. The results of this study will benefit scholars, artists, architects and traditional craftsmen concerned with traditional Chinese architectural color painting. It will enable them to gain a more in-depth understanding of the pattern design methods and artistic thematic content of Baofujin color paintings. It will provide new perspectives and an important reference source for further research on Jiangnan traditional architectural color paintings.